La valoración criminológica como medida socioeducativa obligatoria para el adolescente que ha cometido un delito por precio o promesa remuneratoria - Benítez Granda, Tatiana Dolores (2016)
This research work entitled, "The Socio-criminological assessment as a mandatory measure for the teenager who has committed a crime by Price or promise of remuneration", its development is based on effective the application of the proportionality guarantees provided for in Article 319. the Code of Childhood and Adolescence ensuring juvenile offenders due proportionality between the offense and the socio attributed measure applied by the crime. This rule is related to Article 76 paragraph 6 of the Constitution of the Republic, which establishes the proper proportion between offenses and criminal, administrative or other sanctions.; ie the Constitution mandates that juvenile offenders be imposed proportionate to the offense educational measures, this is corroborated by the Art. 77 Section 13 of the Constitution which provides for juvenile offenders proportional system governed social and educational measures to infringement attributed. The State shall determine by law custodial and non-custodial sanctions. The deprivation of liberty shall be established as a last resort for the minimum necessary period, and will be held in separate institutions to those of adults. So far we have observed the warranty offenders teenager in implementation of socio-educational measures, however when we find young offenders killing other person for payment or promise, are imposing the same measures, while measures socio aim the protection and development of juvenile offenders as stipulated in Article 371 of the Code of Childhood and Adolescence.; this has not been met, the intellectual development of young 6 offenders not considered, criminological assessment should realizársele from the start of the criminal trial, during and after the implementation of socio-educational measures in order to achieve rehabilitate their criminal behavior, it is known the Art. 385 paragraph 3 of the Code of Childhood and Adolescence states for cases of crimes punishable by imprisonment for more than ten years imprisonment, the measure warning and institutional placement of four to eight years will be applied, in addition to six months before rehabilitative measure concluding this comprehensive evaluation to determine the need for monitoring and control of up to two years following the implementation of the measures will take place; This rule is intended to ensure the rehabilitation of the teenager who has committed a crime of imposing killings of 4-8 years of institutional confinement, however, it has not scheduled during execution teenage expect a criminological assessment of their illegal conduct in order to achieve change their state of danger and become useful to society. Therefore considers this measure to be introduced in the criminological study teenager when immersed in crimes against the lives of people. The development of literature and the results of the survey and interviews allowed me to get criteria, with clear and precise basis of well known literature, which contributed to the verification of objectives, and the testing of the hypothesis, allowing support changes proposed the Organic Code of Childhood and Adolescence. The content of the thesis is the result of an arduous our legal research in the scientific, legal, social and methodological level, which deals with theories and knowledge obtained through legal research techniques.